2015
DOI: 10.3136/fstr.21.67
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Profile of Furanocoumarins from the Ribbed Celery (<i>Apium Graveolens</i> L Var. <i>Dulce</i> Mill./ Pers.)

Abstract: The aim of this study was to identify and determine the qualitative and quantitative composition of furanocoumarins in anatomical parts (blade and petiole) of two cultivars of ribbed celery, depending on the age of the plant . Two accurate, precise and inexpensive techniques for analytical detection of coumarin in a relatively short period of time were used in the present study. TLC -the method considered as preliminary, showed the presence of psolaren, bergapten, xanthotoxin and simple coumarin -umbelliferone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Celery seed‐derived oil has been extracted to repel lesser grain borer, dengue vector, mosquito and bacteria (Baananou et al ., 2013; Ebadollahi, 2018; Kumar et al ., 2014; Tuetun et al ., 2004). In addition, celery and other Apiaceae species are rich in coumarins and their derivatives (Najda et al ., 2015; Numonov et al ., 2018; Poumale et al ., 2013; Zobel and Brown, 1990), a major group of plant secondary metabolites with multiple pharmaceutical activities and important roles in defence against pathogens (Carpinella et al ., 2005; Chong et al ., 2002; Figueroa‐Guinez et al ., 2015; Kontogiorgis et al ., 2006; Stanchev et al ., 2008; Sun et al ., 2015). Here we showed that several genes of the coumarin biosynthesis pathway in celery and some other Apiaceae species were expanded in copy number compared with Arabidopsis and other studied non‐Apiaceae species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Celery seed‐derived oil has been extracted to repel lesser grain borer, dengue vector, mosquito and bacteria (Baananou et al ., 2013; Ebadollahi, 2018; Kumar et al ., 2014; Tuetun et al ., 2004). In addition, celery and other Apiaceae species are rich in coumarins and their derivatives (Najda et al ., 2015; Numonov et al ., 2018; Poumale et al ., 2013; Zobel and Brown, 1990), a major group of plant secondary metabolites with multiple pharmaceutical activities and important roles in defence against pathogens (Carpinella et al ., 2005; Chong et al ., 2002; Figueroa‐Guinez et al ., 2015; Kontogiorgis et al ., 2006; Stanchev et al ., 2008; Sun et al ., 2015). Here we showed that several genes of the coumarin biosynthesis pathway in celery and some other Apiaceae species were expanded in copy number compared with Arabidopsis and other studied non‐Apiaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an important vegetable, celery has many pharmacologically active compounds, including flavonoids, volatile oils, unsaturated fatty acids and others (Lin et al ., 2007; Sellami et al ., 2012). It is rich in coumarins and their derivatives (Najda et al ., 2015; Numonov et al ., 2018; Poumale et al ., 2013; Zobel and Brown, 1990), having prominent roles in defending against pathogens (Carpinella et al ., 2005; Chong et al ., 2002; Figueroa‐Guinez et al ., 2015; Sun et al ., 2015) and multiple pharmaceutical activities, such as anticoagulation, antibacterial and anti‐inflammatory properties (Kontogiorgis et al ., 2006; Stanchev et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furocoumarins inhibit the calcium channel, reduce platelet aggregation [ 9 ], induce apoptosis in human promyelocytic leukaemia [ 10 ] and show hepatoprotective effects [ 11 ]. Imperatorin has been reported to have numerous potent pharmacological actions, including anti-inflammation [ 12 ], anti-bacterial [ 13 ], anti-allergic [ 14 ], beneficial cardiovascular effects [ 15 , 16 , 17 ], neuromodulation [ 18 , 19 , 20 ] and is able to induce apoptosis in human promyelocytic leukaemia and HL-60 cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that plant compounds play an important role in both the prevention and treatment of cancers. These compounds work by different mechanisms; however, the induction of apoptosis is a common point of many of these compounds [ 38 ]. The effect of coumarins on the cytotoxic effect of members of the Apicaceae family has also been proven in studies [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%